MAJELIS GEREJA BERBASIS KESETARAAN GENDER: Studi Kasus Di GKPS Lubuk Pakam Kota, Resort Lubuk Pakam Distrik VIII Sumatera Utara (2021-2022) - Purba, Michael Rony (Jurnal Pendidikan Kristen dan Ilmu Teologi Marturia, 2022)
AbstractServing like Christ is the basis of service for Christians. It grows out of genuine love for God, and for others. In the GKPS structure, each congregation must have a position called the Assembly. The assembly is in charge of preserving God's Word, preaching, attending sermons, and performing social services to the congregation. In that case, the author's research leads to the Lubuk Pakam City GKPS Congregation Council, Lubuk Pakam Resort, District VIII, North Sumatra. The main purpose of this paper is to see whether the implementation of services has been based on gender equality? The reason why the author wrote this article is that women's councils often do not receive strong support from their families. The role of women in Simalungun Batak Culture in the household is very much a reason. However, what is interesting is that the pressure of women's councils in the family becomes their encouragement, motivation, and enthusiasm for these people in carrying out every service activity in the service of the Church. The author's data collection will use the qualitative method. Talking, observation, and analysis of findings through human behavior observed in the field, as well as results of interviews, and research recordings are the methods of this research as well. Abstrak Melayani seperti Kristus adalah dasar pelayanan bagi orang Kristen. Hal itu tumbuh dari kasih yang tulus kepada Allah, dan sesama. Dalam struktur GKPS, setiap jemaat harus memiliki jabatan yang disebut Majelis. Majelis bertugas memelihara Firman Tuhan, berkhotbah, menghadiri sermon, serta melakukan pelayanan sosial kepada jemaat. Dalam hal itu, penelitian penulis mengarah kepada Majelis Jemaat GKPS Lubuk Pakam Kota, Resort Lubuk Pakam, Distrik VIII, Sumatera Utara. Tujuan utama tulisan ini melihat, apakah dalam pelaksanaan pelayanan sudah berbasis kesetaraan gender? Alasan penulis mengangkat tulisan ini mengingat majelis perempuan sering tidak mendapat dukungan kuat dari keluarga. Peranan perempuan dalam Budaya Batak Simalungun di rumah tangga sangat banyak menjadi sebuah alasan. Namun yang menarik adalah ketertekanan majelis perempuan dalam keluarga menjadi dorongan, motivasi, dan semangat tersendiri bagi kaum ini dalam melakukan setiap kegiatan pelayanan di dalam pelayanan Gereja. Pengumpulan data penulis akan memakai metode Kualitatif. Temu bual, pemerhatian, dan analisis temuan melalui tingkah laku manusia yang diamati di lapangan, serta hasil wawancara, dan rekaman penelitian menjadi metode penelitian ini juga.